Identifying predictors of programming achievement - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2007)
The main purpose of this study is to explore the predictors of programming achievement. With this aim in mind, the students' achievement in the programming courses is specified as the dependent variable and computer achievement, creativity, problem solving, general aptitudes, computer attitudes and mathematics achievement are specified as the independent variables. A correlational design was used to explain the relations between dependent and independent variables. The study group consists of 48 high school students in Profilo, Anatolia Technical High School, Istanbul. At the end of the study, significant relations were found between the students' programming achievement and their computer achievement, general aptitudes and mathematics achievement. Also, in order to determine the predictors of the students' programming achievement, multiple regression analysis was applied. The findings reveal that only one variable that significantly predicts the students' programming achievement is general aptitude.
Keywords: programming achievement; creativity; problem solving; general aptitudes; computer attitude; mathematics achievement; SUCCESS